The role of Ukraine in the total alcohol export from Russia since the first half of XIX till the beginning of XX centuries - Пилипенко О. (Київський національний університет імені Тараса Шевченка, 2007)
Scientific article devoted export of spirit from Ukraine in second part of XIX – in the beginning of XX cent. Author had made scientific analysis of Ukrainian regions role in Russian empire export of spirit.

Досліджено експорт спирту з України у другій половині ХІХ – на початку ХХ ст. Проаналізовано роль українських губерній у загальноросійському вивозі спирту.
Роль України у загальному експорті спирту з Росії у другій половині ХІХ – на початку ХХ століття